ANTESEEDEN DAN KONSEKUENSI DARI SEVERITY OF OTHER CUSTOMER FAILURE - Nina Budiwati; Asep Hermawan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
The background of this research was to conduct a profound study of impact of other-customer failure The purpose of this paper is to investigate how and why other-customer misbehavior has a negative influence on customer satisfaction with the service firm.The objectives of this research was : (a) the effect of controllability to firm responsibility, (b) the effect of stability to firm responsibility, (c) the effect of firm responsibility to customer satisfaction, (d) the effect of firm responsibility to service recovery expectations, (e) the effect of service recovery expectations to customer satisfaction, (f) the effect of severity of other customer failure to service recovery expectations, (g) the effect of severity of other customer failure to customer satisfaction, (h) the effect of perceived employee effort to customer satisfaction.The design of this research applies a survey toward unit of analysis on hotels services by interview the customers for testing hypothesis. Meanwhile the required data consist of seventh variables which arecontrollability attributions, stability attributions, firm responsibility, service recovery expectation, severity of other customer failure, perceived employee effort and customer satisfaction. The aggregatenumbers of hotels guests being respondent of the study are 200. Data analysis used in this research was consists of Structural Equation Model Analysis by AMOS 6 as software.The result of this research conclude that controllability and stability attributions had an effect to firm responsibility, firm responsibility had an effect to service recovery expectations, severity of othercustomer failure had an effect to service recovery expactations, and perceived employee effort had an effect to customer satisfaction. Meanwhile firm responsibility had an effect to customer satisfaction,service recovery expectations had an effect terhadap customer satisfaction, severity of other customer failure had an effect to customer satisfaction.Keywords: Service recovery expectations, severity of other customer failure, and customer satisfaction